Negotiating relationships: village to city, beadwork to SMS - Jolles, F. (Southern African Humanities, 2021)
The article traces the evolution of different modes of communication among adolescents and young adults as they affect the formation of personal relationships in rural and peri-urban communities. Starting with the colour- and motif-coded beadwork messages of preliterate times it goes on to examine the impact of the spread of literacy on the beadwork of the 1960s and 1970s, the projection of gestures through photographs and, finally, the arrival of the technological revolution of the 1990s and the use of cellular phones for the transmission of text messages or SMSs (from Short Message Service). The new modes of communication and their effects on the individuals making use of them are linked to contemporary social changes and the inevitable stresses of living in a transitional society in which the values and support systems codified in the kinship system of the old order are progressively eroded without being replaced by new norms. To cite this article: Jolles, F. 2006. Negotiating relationships: village to city, beadwork to SMS. Southern African Humanities 18 (2): 119-38.